Economic Status, Knowledge Level, and Physical Condition of the House with the Incidence of Pulmonary Tuberculosis - Maria Adelheid Meo; Marylin Susanti Junias; Honey Ivon Ndoen (Journal of Health and Behavioral Science, 2022)
Tuberculosis is a directly infectious disease caused by the bacterium Mycobacterium Tuberculosis. During the last three years, most patients with pulmonary tuberculosis were at the Kambaniru Health Center. The purpose of this study was to determine the relationship between economic status and the incidence of pulmonary tuberculosis, to determine the level of knowledge about the incidence of pulmonary tuberculosis, and to determine the relationship between the physical condition of the house and the incidence of pulmonary tuberculosis. This research is an analytic observational study with a case-control research design. The sample in this study was 110 people, consisting of 55 cases and 55 controls. The data obtained were analyzed using the Chi-square test. The results showed that there was a significant relationship between economic status (0.001), level of knowledge (0.022), type of floor (0.001), temperature (0.001), and the incidence of pulmonary tuberculosis. There is no relationship between occupancy density (0.095), ventilation (0.096), humidity (0.233), and the incidence of pulmonary tuberculosis. Therefore, there is a need for cooperation between the government, public health center officers, and the community so that efforts can be made to reduce tuberculosis cases at the Kambaniru Health Center.